MD or not MD - Arno Zaritsky; A. James Beyer (Critical Care Medicine, 1992)
BACKGROUND: Direct acting oral anticoagulants (DOACs) are widely utilized in the management of venous thromboembolism. Numerous studies have demonstrated that their safety and efficacy surpass those of warfarin. Nevertheless, the evidence supporting their use in treating venous thrombosis among patients with morbid obesity remains inadequate, necessitating further investigation. METHODS: A comprehensive computer search was performed for studies on direct acting oral anticoagulants for venous thrombosis in patients with morbid obesity, published in the Cochrane Library, PubMed, and Embase databases prior to June 20, 2026. The quality of the literature was assessed using the Cochrane risk-of-bias tool and the Newcastle-Ottawa Scale. Meta-analysis was conducted utilizing RevMan 5.3 software, focusing on recurrent thromboembolic events, any bleeding event, and major bleeding events as outcome metrics. RESULTS: A total of 1251 studies were retrieved, with 20 ultimately included, encompassing 44,672 morbidly obese VTE patients. Among them, 18,433 were in the direct acting oral anticoagulants group, and 26,239 were in the warfarin group. The results of the meta-analysis indicate that direct acting oral anticoagulants may have a lower risk of thrombosis recurrence (OR = 0.74, 95% confidence interval [CI]: 0.59-0.92, P < .01) and total bleeding (OR = 0.72, 95% CI: 0.66-0.77) compared to warfarin. The risk of major bleeding (OR = 0.69, 95% CI: 0.60-0.80, P < .01) with direct acting oral anticoagulants may be lower than that with warfarin. Subgroup analysis indicated that standard doses of DOACs were more effective than warfarin in managing VTE in patients with morbid obesity, while maintaining comparable safety levels. Dosage adjustments may not be necessary. In the treatment of morbidly obese patients with venous thromboembolism, rivaroxaban demonstrates a thrombosis recurrence risk similar to warfarin but a lower risk of major bleeding. Similarly, the use of apixaban in this patient population shows reduced risks of both thrombosis recurrence and major bleeding compared to warfarin. CONCLUSION: The safety and efficacy of direct acting oral anticoagulants in the treatment of venous thromboembolism in patients with morbid obesity may be superior to warfarin.